Predictors for functional and anatomic outcomes in macular edema secondary to non-infectious uveitis. - Jessica Matas; Victor Llorenç; Alex Fonollosa; Cristina Esquinas; David Diaz-Valle; Barbara Berasategui; Marina Mesquida; Joseba Artaraz; Jose Rios; Alfredo Adan (PLoS ONE)
Aims We aimed to investigate predictive factors for visual and anatomic outcomes in patients with macular edema secondary to non-infectious uveitis. Material and methods We conducted a multicenter, prospective, observational, 12-month follow-up study. Participants included in the study were adults with non-infectious uveitic macular edema (UME), defined as central subfoveal thickness (CST) of >300 μm as measured by spectral domain optical coherence tomography (SD-OCT) and fluid in the macula. Demographic, clinical and tomographic data was recorded at baseline, 1, 3, 6 and 12 months. Foveal-centered SD-OCT exploration was set as the gold-standard determination of UME using a standard Macular Cube 512x128 A-scan, within a 6 x 6 mm2 area, and the Enhanced High Definition Single-Line Raster. To assess favorable prognosis, the main outcomes analyzed were the best-corrected visual acuity (BCVA) and the CST. Favorable prognosis was defined as sustained improvement of BCVA (2 lines of gain of the Snellen scale) and CST (decrease of 20% of the initial value or <300 μm) within a 12 month period. Results Fifty-six eyes were analyzed. The number of eyes with sustained improvement in the CST was 48 (86.2%), against 23 (41.1%) eyes with sustained improvement in BCVA. Favorable prognosis, as defined above, was observed in 18 (32.1%) eyes. UME prognosis was negatively correlated with baseline foveal thickening, alteration in the vitreo-macular interface and cystoid macular edema. In contrast, bilaterally, systemic disease and the presence of anterior chamber cells were predictive of favorable prognosis. Conclusion Available treatment modalities in UME may avoid chronic UME and improve anatomic outcome. However, the proportion of functional amelioration observed during 12 months of follow-up is lower. Thicker CST, alteration in the vitreo-macular interface and cystoid macular edema may denote less favorable prognosis. Conversely, bilaterally, systemic disease and anterior chamber cells may be associated with favorable prognosis in UME.